Novel approach for CO2-enriched natural gas dehydration via adsorption using 13X zeolite as solid desiccants - Firas, A.A.K. (Maney Publishing, 2014)
Natural gas has attracted high attention in the last few decades because of the increasing demand for alternative energy sources owing to depleting conventional energy sources. Raw natural gas consists of several components (light, heavy and aromatic hydrocarbons) and contaminants (i.e. water, CO2, H2S, mercury, N2 and many others) that need to be processed and purified before it is introduced to the market. Water vapour is considered one of the most important contaminants in natural gas. Water vapour needs to be removed before further processing because it might be the main reason for blockage or corrosion of pipelines and facilities as its existence can lead to the creation of natural gas hydrates. Adsorption among other alternative techniques is one of the most efficient and cost-effective processes. Zeolites have shown high potential and sustainability among other solid desiccants in terms of high adsorption capacity, low regeneration costs and high selectivity. The results show that the adsorption capacity of the 13X zeolite increased with the increasing of operating pressure of the particular experiment. The experiments have been done at several operating pressures (2, 4, 6 and 8 bar). At 8 bar the results showed the peak value of the adsorbent capacity even with the highest content percentage of CO2 in the dualphase gaseous and vapour mixture. Â© 2014 W. S. Maney & Son Ltd.